Xenophobic Attack in South Africa: an Impediment to Love and Tolerance as Dynamics of African Cultural Unity and The Out - Bello Yekeen; Tunde-Awe Bolajoko Margaret; Yunus Aliyu (Universitas Pendidikan Ganesha, 2024)
The issues of xenophobia and conflict in Africa remain significant challenges to achieving peace and sustainable development. This study aims to examine the concepts of love and tolerance as essential arts that can serve as a central force for fostering peace in Africa. Love is understood as the divine essence that creates and unites all things, while tolerance is considered its derivative, supporting harmony in human existence. The study employs a qualitative method, with data collected through literature reviews and historical analyses of the colonial impact on the values of love, tolerance, and interpersonal relationships in Africa. The findings reveal that love and tolerance are mutually reinforcing qualities essential for establishing peace and social harmony. However, colonialism prioritized the exploitation of natural resources and the division of African societies, thereby hindering the cultivation of these values. The study concludes by emphasizing the importance of fostering an environment that promotes unity by encouraging Africans to accept one another as brothers, transcending national, religious, and cultural differences. It recommends that African governments develop policies and create environments that allow individuals to live and work across the continent without discrimination, provided legal requirements for migration and residency are met. These measures aim to reduce xenophobic tendencies and promote sustainable peace and development in Africa.